2006
DOI: 10.1021/bp050255m
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Models To Study the Impact of Mixing on a Fed-Batch Culture of Saccharomyces cerevisiae

Abstract: The mechanisms of interaction between microorganisms and their environment in a stirred bioreactor can be modeled by a stochastic approach. The procedure comprises two submodels: a classical stochastic model for the microbial cell circulation and a Markov chain model for the concentration gradient calculus. The advantage lies in the fact that the core of each submodel, i.e., the transition matrix (which contains the probabilities to shift from a perfectly mixed compartment to another in the bioreactor represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 16 publications
(33 reference statements)
2
22
0
Order By: Relevance
“…In order to calculate accurately the dextrose concentration gradient, the intermittent behaviour of the pump must be considered [33]. Therefore, a pulse matrix was used to represent the discontinuous behaviour of the pump, in which the number of columns corresponded to the number of transitions, and the number of rows to the number of states.…”
Section: Sub-model 1: Fluid Mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to calculate accurately the dextrose concentration gradient, the intermittent behaviour of the pump must be considered [33]. Therefore, a pulse matrix was used to represent the discontinuous behaviour of the pump, in which the number of columns corresponded to the number of transitions, and the number of rows to the number of states.…”
Section: Sub-model 1: Fluid Mixingmentioning
confidence: 99%
“…The deterministic method is based on the consideration of differential equations that define the flows between the compartments, while the stochastic approach allows the inclusion of the probabilistic nature of the mixing process and the circulation of particles in the reactor to be traced [32]. The advantage of such a model is that both representation of the circulation of the microorganisms and fluid mixing can be performed using the same structure [33].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, tracer test involving particulate dye instead of soluble dye has been recently recognized as more relevant to describe the transport of microbial cells (Asraf-Snir, 2011). We have also use this method previously for the characterization of the transport of fluorescently labeled microbial cells in scale-down reactors (Delvigne, 2006b). Our methodology has been improved in the present work, mainly at the level of the method used to detect fluorescent particles.…”
Section: Tracer Test For the Determination Of The Residence Time Distmentioning
confidence: 99%
“…However, previous hydrodynamic results have shown that the passage of the cells from mixed to non-mixed part of the P-SDR is strongly stochastic [13]. In order to take this important feature into account, a second air valve control algorithm has been elaborated on the basis of a two-compartment stochastic hydrodynamic model developed in our laboratory [14]. Samples of the two controlling schemes are shown at Fig.…”
Section: Effect Of the Dissolved Oxygen Level Fluctuations: Involvemementioning
confidence: 99%